Step (1): Assume given statement
Let the given statement be P(n), i.e.,
P(n):1⋅2+2⋅3+3⋅4+⋯+n(n+1)=n(n+1)(n+2)3
Step (2): Checking statement P(n) for n=1
Put n=1 in P(n), we get
P(1):1⋅2=1⋅(1+1)(1+2)3
⇒2=1⋅2⋅33
⇒2=2
Thus P(n) is true for n=1
Step (3): P(n) for n=K
Put n=K in P(n) and assume this is true for some natural number K i.e.,
P(K):1⋅2+2⋅3+3⋅4+⋯+K(K+1)
=K(K+1)(K+2)3 ⋯(1)
Step (4): Checking statement P(n) for n=K+1
Now, we shall prove that P(K+1) is true whenever P(K) is true
Now, we have
1⋅2+2⋅3+3⋅4+⋯+K(K+1)+(K+1)(K+2)
=K(K+1)(K+2)3+(K+1)(K+2) (Using (1))
=(K+1)(K+2)(K3+1)
=(K+1)(K+2)(K+3)3
We can write it as,
=(K+1){(K+1)+1}{(K+1)+2}3
Thus, P(K+1) is true whenever P(K) is true.
Final Answer :
Hence, from the principle of mathematical induction, the statement P(n) is true for all n∈N.